PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V UPT SD NEGERI 060971 KEMENANGAN TANI TAHUN PEMBELAJARAN 2025/2026 - Reh Syerina Br Bangun; Ester Julinda Simarmata; Paska Sriulina Tarigan; Reflina Sinag; Eka Margareta Sinaga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on the IPAS learning outcomes of Grade V students at UPT SD Negeri 060971 Kemenangan Tani in the 2025/2026 academic year. This study employed a quantitative method with a one-group pretest-posttest design, involving 25 students as the sample. Data collection techniques included tests, questionnaires, observations, and documentation. The results of the study showed that the pretest results in Grade V had an average score of 57, which was categorized as low, while the posttest average score increased to 85.04, which was categorized as high. Furthermore, hypothesis testing using the t-test obtained a t-value greater than or equal to the t-table value, namely 22.876 ≥ 2.069. Therefore, it can be concluded that the implementation of the Problem Based Learning (PBL) model significantly improves students’ learning outcomes in the IPAS subject.